Protocol for a longitudinal qualitative interview study: maintaining psychological well-being in advanced cancer—what can we learn from patients' and carers' own coping strategies?. Issue 6 (17th June 2013) - Roberts, Diane; Appleton, Lynda; Calman, Lynn; Large, Paul; Grande, Gunn; Lloyd-Williams, Mari; Walshe, Catherine
Abstract : Introduction: People with advanced cancer and their carers experience stress and uncertainty which affects the quality of life and physical and mental health. This study aims to understand how patients and carers recover or maintain psychological well-being by exploring the strategies employed to self-manage stress and uncertainty. Methods and analysis: A longitudinal qualitative interview approach with 30 patients with advanced cancer and 30 associated family or informal carers allows the exploration of contexts, mechanisms and outcomes at an individual level. Two interviews, 4–12 weeks apart, will not only enable the exploration of individuals' evolving coping strategies in response to changing contexts but also how patients' and carers' strategies inter-relate. Patient and Carer focus groups will then consider how the findings may be used in developing an intervention. Recruiting through two major tertiary cancer centres in the North West and using deliberately broad and inclusive criteria will enable the sample to capture demographic and experiential breadth. Ethics and dissemination: The research team will draw on their considerable experience to ensure that the study is sensitive to a patient and carer group, which may be considered vulnerable but still values being able to contribute its views. Public and patient involvement (PPI) is integral to the design and is evidenced by: a research advisory group incorporating patient and carers, prestudy consultations with the PPI group at one of the study sites and a user as the named applicant. The study team will use multiple methods to disseminate the findings to clinical, policy and academic audiences. A key element will be engaging health professionals in patient and carer ideas for promoting self-management of psychological well-being. The study has ethical approval from the North West Research Ethics Committee and the appropriate NHS governance clearance. Registration: National Institute for Health Research (NIHR) Clinical Studies Portfolio, UK Clinical Research Network (UKCRN) Study number 11725.